中国高校文物保护本科专业发展历程与 课程体系建设 ——以西北大学文物保护专业为例. - 杨 璐 (China Cultural Heritage, 2025)
To understand the development and problems in tertiary education relating to cultural heritage conservation that offers bachelor’s degree in China and corresponding curriculum, this paper reviews the background and demand for the establishment of cultural heritage conservation as a discipline during different times in China since the 1950s, and the process during which specific historical opportunities facilitated the creation of cultural heritage conservation as a special subject for tertiary education program in China based on the cultural heritage conservation research center of the Northwest University of China, as well as the development of this major from the 1990s to this century. After analyzing current curriculums provided by tertiary education institutions for bachelor’s degree on cultural heritage conservation, this paper identifies two types, namely, science-based and art-based. The science-based program for developing skilled professionals in cultural heritage conservation is characterized by the integration of science and engineering with humanity and social sciences. The curriculum for a bachelor’s degree includes five modules, namely, general education courses, basic courses for the discipline, core curriculum for the major, elective courses for the major, and practice courses. Taking the major of technologies for cultural heritage conservation at Northwest University as an example, this paper introduces the components of credits for various classes, an innovative model developed by Northwest University for cultural heritage conservation, which combined practices with teaching, and the latest trend in curriculum structure developed by Northwest University relating to cultural heritage conservation. The art-based program for developing skilled professionals of in cultural heritage conservation is characterized by its focus on the restoration of artwork, combined with the science and knowledge relating to cultural heritage conservation. Compared to the science-based program, the art-based program for a bachelor’s degree has modules with different names, but similar structures. The differences between the two programs are mainly in three modules, namely, basic courses for the discipline, key courses for the major, and elective courses for the major. Taking the major of Conservation and Restoration of Cultural Heritage of Nanjing University of Arts as an example, this paper introduces the components of credits for various courses and the latest development trends in the curriculum. Based on the development of the curriculum for a bachelor’s degree in cultural heritage conservation, this paper addresses current demands for the following: teaching and learning across multiple disciplines relating to cultural heritage conservation, teaching staff with rich experience and special knowledge, standardized textbooks, laboratories, instruments, equipment, and other facilities. Taking Northwest University as an example, it finds that in recent years Northwest University has taken actions to facilitate education on cultural heritage conservation, including utilizing resources in the industry to improve the quality of practice, teaching, and learning, grasping the opportunities brought by the reforms to enhance curriculum development, driving the editing of series of textbooks by utilizing resources in the industry. This paper hopes to serve as a reference for the future development of education for a bachelor’s degree in cultural heritage conservation.